Estimating Changing Marshland Habitat and Conservation Potential for Diamondback Terrapins (Malaclemys terrapin) in New Jersey under Climate Change - Jacqueline R. Ganter; Zachary Christman (Land, 2023)
The diamondback terrapin (Malaclemys terrapin), a brackish water turtle species native to the eastern United States, is under “special concern” in the state of New Jersey, due to decreasing habitat from development and changing climatic conditions. Diamondback terrapins reside in saline marshes and coastal wetlands and nest in sandy substrate, primarily beaches and dunes, in June and July. New Jersey is vulnerable to sea level rise, leaving diamondback terrapin habitats and nesting areas at risk of inundation under future climate scenarios, and, as the most densely populated state, subject to continual development pressures on potentially conservable land. Changing sea levels and climatic conditions will cause accretion and migration of marshes into open grassy land, yielding new potential terrapin habitats, though changing temperatures could affect the availability of male-producing nesting sites and impact potential nesting patterns. This study spatially modeled lost, gained, and changed habitat and nesting areas under sea level rise scenarios for 2050 and 2100 in New Jersey and quantified these by municipality to offer insights into potential conservable land that may mitigate these changes for the vulnerable species. The results indicate an overall decrease in potential habitat coupled with a decrease in both overall and male-producing nesting ranges.